2017
DOI: 10.1186/s12981-017-0152-0
|View full text |Cite|
|
Sign up to set email alerts
|

Hospital days attributable to immune reconstitution inflammatory syndrome in persons living with HIV before and after the 2012 DHHS HIV guidelines

Abstract: BackgroundImmune reconstitution inflammatory syndrome (IRIS) can manifest with initiation or reintroduction of antiretroviral therapy (ART) in persons living with HIV (PLWH). In 2012, updated United States treatment guidelines recommended initiation of ART for all PLWH regardless of CD4 count. The objectives of this study were to quantify hospital usage attributable to IRIS and assess the reasons for hospitalization in PLWH before and after the guideline update.MethodsSubjects were PLWH between 18–89 years of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Second, we found that cardiovascular, renal and pulmonary CMs, as well as HCV coinfection, are significantly associated with an increased risk of acute hospitalizations among PWL-HIV, in line with other reports in the literature. 18 , 20 , 46 , 48 These findings contribute to the idea that a more stringent control of such CMs may well be necessary in the setting of chronic management of HIV infection. Although much has been done in terms of research and development of newer antiretrovirals, with a more favorable profile of toxicity in all lines of HAART, efforts to reduce the prevalence of CMs in HIV patients need to be increased rather than reduced.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Second, we found that cardiovascular, renal and pulmonary CMs, as well as HCV coinfection, are significantly associated with an increased risk of acute hospitalizations among PWL-HIV, in line with other reports in the literature. 18 , 20 , 46 , 48 These findings contribute to the idea that a more stringent control of such CMs may well be necessary in the setting of chronic management of HIV infection. Although much has been done in terms of research and development of newer antiretrovirals, with a more favorable profile of toxicity in all lines of HAART, efforts to reduce the prevalence of CMs in HIV patients need to be increased rather than reduced.…”
Section: Discussionmentioning
confidence: 74%
“…Acknowledging the paucity of information about this issue, in our country as well as in other countries, our analysis may be relevant to understand how HIV infection may still be causing health care resources utilization as well as health care expenditure in the present setting, beyond HIV testing, HAART expenditure and continuous efforts to improve high quality retention in care. 18 20 , 46 …”
Section: Discussionmentioning
confidence: 99%
“…Mortality from CM-IRIS can be reduced significantly if patients initiated antiretroviral therapy during the phase of moderate immunosuppression, and before significant CD4+ T cell count loss [134,135]. The morbidity and costs associated with IRIS in people living with HIV continue to decline in the USA since 2012 (< 8%), with no fatality [3]. Although much research is being done on the mechanisms that modulate the immunopathogenesis of CM-IRIS, no biomarkers for this condition have been validated to produce a sufficient level of evidence to enter clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus species are the most common cause of meningitis in adults and one of the leading causes of HIV-related mortality in the world, with a global incidence estimated at 223,100 cases per year [1,2]. In countries with limited resources, cryptococcosis drives up to 40% of all hospitalizations and deaths associated with the advanced stage of HIV infection [3][4][5]. Immune reconstitution inflammatory syndrome (IRIS) associated with cryptococcosis is a common complication that manifests after the initiation of antiretroviral therapy (ART) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cryptococcus species are the most common cause of meningitis in adults and one of the leading causes of human immunodeficiency virus (HIV)-related mortality in the world, with a global incidence estimated at 223,100 cases per year [ 1 , 2 ]. In countries with limited resources, cryptococcosis drives up to 40% of all hospitalizations and deaths associated with the advanced stage of HIV infection [ 3 , 4 , 5 ]. Immune reconstitution inflammatory syndrome associated with cryptococcosis (C-IRIS) is a common complication that manifests after the initiation of antiretroviral therapy (ART) [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%